2011
DOI: 10.1038/ncb2285
|View full text |Cite
|
Sign up to set email alerts
|

esBAF facilitates pluripotency by conditioning the genome for LIF/STAT3 signalling and by regulating polycomb function

Abstract: Signaling by the cytokine LIF and its downstream transcription factor, STAT3, prevents differentiation of pluripotent embryonic stem cells (ESCs) by opposing MAP kinase signaling. This contrasts with most cell types where STAT3signaling induces differentiation. We find that STAT3binding across the pluripotent genome is dependent upon Brg, the ATPase subunit of a specialized chromatin remodeling complex (esBAF) found in ESCs. Brg is required to establish chromatin accessibility at STAT3 binding targets, in esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
334
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(366 citation statements)
references
References 48 publications
31
334
1
Order By: Relevance
“…Previous studies have shown that Ezh2 is required for GC formation and the SWI/SNF complex synergistically regulates several genes together with the Ezh2-PRC2 complex (36)(37)(38)(39). MTA3, a subunit of the NuRD complex, is also known to interact with Bcl-6 and to inhibit Blimp-1 expression (40).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Ezh2 is required for GC formation and the SWI/SNF complex synergistically regulates several genes together with the Ezh2-PRC2 complex (36)(37)(38)(39). MTA3, a subunit of the NuRD complex, is also known to interact with Bcl-6 and to inhibit Blimp-1 expression (40).…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of H3K27me3 levels may indicate a specific repressive role of BAF250a in ES cells. Although Brg1 deletion does not result in global H3K27me3 and H3K4me3 changes, H3K27me3 density decreased in Brg1-repressed genes and increased in Brg1-activated genes in Brg1 KO ES cells (33). These differences in histone modification changes in BAF250a KO and Brg1 KO ES cells reflect distinct functions exercised by esBAF components on histone modification regulations.…”
Section: Discussionmentioning
confidence: 79%
“…Successful development of ESC-based therapies, however, largely depends on our understanding of the genes and pathways that constitute the genetic network governing ESC self-renewal and differentiation. Focused functional studies, over the last two decades, have established Oct4, Sox2, and Nanog as the core transcription factors (18)(19)(20)(21), with epigenetic features (22)(23)(24), miRNAs (25)(26)(27), and telomere maintenance (28) playing key roles in the establishment and the maintenance of the pluripotent state in ESCs. Despite the elucidation of many genes and pathways critical for the maintenance of the pluripotent state, the mechanisms that coordinate the activities of master regulators, key signaling pathways, and epigenetic features remain poorly understood, owing largely to incomplete characterization of the genetic network underlying ESCs.…”
Section: Resultsmentioning
confidence: 99%